Customer Satisfaction as a Priority in Excellent Banking Services - Wulandari, Dita (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The most important thing from a business is the customer, so satisfying and pleasing him is a necessity. The company realizes that the fulfillment of customer needs and desires (both physical and emotional) can give birth to loyal behavior, which has an impact on increasing sales/profits. In the banking business, presenting excellent service performance is one of the efforts to provide satisfaction, so that loyalty is built. This study is intended to analyze the phenomenon of bank customer loyalty through satisfaction by building excellent service and providing added value. The method used to analyze the phenomenon is quantitative with regression statistics as the basis for disclosure. The research subjects were BNI Jakarta bank customers, with a total of 100 correspondents. The data collection technique used purposive method by distributing research questionnaires. The results of the study identify, the most likely opportunity for the birth of loyal behavior is to build satisfaction through service. This happens because the service provides overall satisfaction, both psychological satisfaction and needs.